The atmospheric composition of the ultra-hot Jupiter WASP-178 b observed with ESPRESSO - Damasceno, Y. C.; Seidel, J. V.; Prinoth, B.; Psaridi, A.; Esparza-Borges, E.; Stangret, M.; Santos, N. C.; Zapatero-Osorio, M. R.; Alibert, Y.; Allart, R.; Azevedo Silva, T.; Cointepas, M.; et al. (Astronomy and astrophysics (Berlin), 2024)
Context . Ultra-hot Jupiters (UHJ) have emerged as ideal testbeds for new techniques for studying exoplanet atmospheres. Only a limited number of them are currently well studied, however. Aims . We search for atmospheric constituents for the UHJ WASP-178 b with two ESPRESSO transits. Additionally, we show parallel photometry that we used to obtain updated and precise stellar, planetary, and orbital parameters. Methods . The two transits we obtained were analysed with narrow-band transmission spectroscopy and with the cross-correlation technique to provide detections at different altitude levels. We focused on searching for Na I , H α , H β , H γ , Mg I , and Li I lines in narrow-band data, as well as Fe I and Fe II , and attempted to confirm Mg I with the cross-correlation technique. We corrected for the Rossiter-McLaughlin effect and regions with a low signal-to-noise ratio due to Na I absorption in the interstellar medium. We then verified our results via bootstrapping. Results . We report the resolved line detections of Na I (5.5 σ and 5.4 σ ), Hα (13σ), H β (7.1 σ ), and tentatively Mg I (4.6 σ ). With a cross-correlation, we confirm the Mg I detection (7.8 σ and 5.8 σ ), and we additionally report the detections of Fe I (12 σ and 10 σ ) and Fe II (11 σ and 8.4 σ ) on both nights separately. The detection of Mg I remains tentative, however, because the results on the two nights differ. The results also differ compared with the properties derived from the narrow-band data. Conclusions . None of our resolved spectral lines probing the middle to upper atmosphere shows significant shifts relative to the planetary rest frame. Hα and Hβ exhibit a respective line broadening of 39.6 ± 2.1 km s −1 and 27.6 ± 4.6 km s −1 , however, indicating the onset of possible escape. WASP-178 b differs from similar UHJ by its lack of strong atmospheric dynamics in the upper atmosphere. The broadening seen for Fe I (15.66 ± 0.58 km s −1 ) and Fe II (11.32 ± 0.52 km s −1 ) might indicate the presence of winds in the mid-atmosphere, however. Future studies of the impact of the flux variability caused by the host star activity might shed more light on the subject. Previous work indicated the presence of SiO cloud-precursors in the atmosphere of WASP-178 b and a lack of Mg I and Fe II . However, our results suggest that a scenario in which the planetary atmosphere is dominated by Mg I and Fe II is more likely. In light of our results, we encourage future observations to further elucidate these atmospheric properties.